Office of Diversity, Equity, and Inclusion: Engagement and Leadership Opportunities for Trainees - Nicole Del Castillo; John Paul Piserchio; Cheryl Brewster; Denise Martinez; John Paul Sánchez (Association of American Medical Colleges, 2022)
Introduction To achieve a healthier future for all, improving diversity through efforts such as diversifying faculty and leadership in academic medicine is imperative. Therefore, medical trainees (medical students, residents, fellows) from groups underrepresented in medicine (UiM) are encouraged to pursue academic careers and have opportunities to gain faculty leadership skills during their training. Trainees also need exposure to the leadership positions within various offices of an academic institution such as the Office of Diversity, Equity, and Inclusion (DEI). The goal of this module is to expose UiM trainees to the Office of DEI and leadership competencies that can be obtained via service and leadership opportunities with it. Methods The Kern model was used in the development, implementation, and evaluation of this 75-minute workshop. The workshop consisted of a PowerPoint presentation, reflection exercises, and case discussion to raise trainees' awareness of the Office of DEI and opportunities to become engaged with and develop faculty leadership competencies through the office. Results Sixty-six diverse learners across three sites completed pre- and postworkshop surveys. Ninety-five percent of participants agreed or strongly agreed that the learning objectives of the workshop had been met. Discussion Overall, this interactive workshop facilitated learners' awareness of the responsibilities of the Office of DEI and opportunities for learners to develop faculty leadership competencies through engagement. Although primarily evaluated among medical students, the module can be of use to learners and faculty of other health professions programs with an Office of DEI.